Electron-impact multiple ionization of Ne, Ar, Kr and Xe - Montanari, Claudia Carmen (2014)
This work describes the multiple ionization cross sections of rare gases by electron-impact. We pay special attention to the high energy region (0.1?10 keV) where the direct ionization is a minor contribution and the post-collisional electron emission dominates the final target charge state. We report here electron-impact single to sextuple ionization cross sections and total ionization cross sections including direct and post-collisional processes, even in the total values. We use the continuum distorted wave and the first Born approximations adapted to describe light-particle impact, i.e. energy, mass and trajectory corrections are incorporated, the latter by considering the electron-target potential and by using the Abel transformation. Auger-type post-collisional contributions are included in the multinomial expansion through experimental branching ratios after single ionization events. Tabulations of these experimental branching ratios for all the orbitals of the four targets are included. Present results are compared with the large amount of electron-impact experimental data available. We have obtained a good description of the multiple-ionization measurements at high energies, where the post-collisional ionization dominates. At intermediate energies, our theoretical results show the correct tendency, with the electron-impact ionization cross sections being far below the proton-impact ones.